MULTIMEDIA INTERAKTIF PENGENALAN HEWAN DAN TUMBUHAN LANGKA MENGGUNAKAN MODEL TUTORIAL - Sembiring, Evaliata Br; Wahyuni, Dwi; Anurogo, Wenang (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2018)
Knowledge of endangered animals and plants is very important for children. Material about those two begins to be studied in class III at the elementary school. A book is used as a medium to deliver the materials. This resulted in a lack of understanding of students toward knowledge about endangered animals and plants. One of the solutions being made is to use the interactive learning media. This paper elaborates on the creation of interactive multimedia learning containing text, images, sound, and animation of 2D. The research shows that: (1) Interactive multimedia is created in the form of tutorials and practice questions in the .exe format so that their use does not depend on a specific software; (2) the aspect of interest-ness of the multimedia is 82.4%; (3) pretest and post-tests show that the interactive multimedia experience increased the student understanding, namely achieving 50% with the average value of the students' score reaches 83.3%.